2021
DOI: 10.3390/molecules26185468
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Interaction between Whey Proteins and Proanthocyanidins and Its Protective Effects on Proanthocyanidins during In-Vitro Digestion and Storage

Abstract: Whey proteins and oligomeric proanthocyanidins have nutritional value and are widely used in combination as food supplements. However, the effect of the interactions between proanthocyanidins and whey proteins on their stability has not been studied in depth. In this work, we aimed to characterize the interactions between β-Lactoglobulin (β-LG) and α-lactalbumin (α-LA) and oligomeric proanthocyanidins, including A1, A2, B1, B2, B3, and C1, using multi-spectroscopic and molecular docking methods. Fluorescence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Procyanidins are characterized by antioxidant activity and the ability to specifically bind proteins and regulate cellular signaling pathways. Therefore, they are effective in preventing various diseases such as cancer, inflammation, cardiovascular disease, diabetes, and autoimmune diseases [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Procyanidins are characterized by antioxidant activity and the ability to specifically bind proteins and regulate cellular signaling pathways. Therefore, they are effective in preventing various diseases such as cancer, inflammation, cardiovascular disease, diabetes, and autoimmune diseases [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have characterized the secondary structures of the purified forms of the primary proteins in whey, α-lactoglobulin and β-lactoglobulin. α-Lactoglobulin, which comprises 20% of whey proteins, features 27.6% α-helices, 23.8% β-sheets, 12.6% β-turns and 36.07% random coil, while β-lactoglobulin, which comprises 60% of whey proteins, features 27% α-helices, 29.7% β-sheets, 18.8% β-turns and 24.67% random coil [ 67 ]. By contrast, hemp protein isolate has been estimated to comprise 17.4% α-helix, 26% β-sheet, 10% β-turns and 36% random coil [ 51 ], while pea protein comprises 8% α-helix, 32% β-sheet, 15% β-turn and 45% random coil [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…thought to be primarily the result of gut microbial metabolism, where their low molecular weight derivatives can then act locally or be absorbed to exert systemic effects [61]. Thus, the formation of a protein-polyphenol complex may actually protect the polyphenol through the unstable GI environment, and studies have demonstrated that these complexes can be used as a delivery vehicle for polyphenols in the development of functional foods [62][63][64].…”
Section: Plos Onementioning
confidence: 99%